New model of PEV parking lots in the presence of demand response uncertainties - Ahmadi, Saeid; Moghaddam, Mahmoud Samiei; Ranjbar, Soheil (Sustainable Energy, Grids and Networks, 2022)
In the presence of today’s environmental concerns, electric transportation services provide significant role of presenting secure and sustainable energy schemes. For this issue, plug-in electric vehicles (PEVs) are an unavoidable part of future smart grids which can provide clear and secure power for different types of electrical energy consumers. In this case, PEVs-based demand response schemes present positive effects of supplying electric powers through smart grid consumers. In the case of evaluating PEV uncertainties, this paper presents a new demand response scheme considering the optimal performance of PEV parking lots through two different reserve markets and electrical energy systems. For this issue, based on the concepts of motivation-based and cost-based demand response programs (DRPs), an adaptive mathematical-based model is developed which considering different time steps, the optimal performance of PEV parking lots are evaluated. Also, based on the performance of several DRPs, the operational performance of PEVs are investigated accurately in which proper participation values with respect to each DRP scheme is estimated. In the case of electricity market uncertainties within different time durations, by using a stochastic-based programming structure, the stochastic performance of PEV parking lots are developed through optimization mathematical model. Numerical results indicate the effectiveness of the proposed approach for optimizing PEV parking lots through different DRPs with considerable effect through supplying sustainable energy.